2014
DOI: 10.2478/aoas-2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protein Concentrate Supplement on the Qualitative and Quantitative Parameters of Milk from Dairy Cows in Organic Farming

Abstract: in our experiment, we studied the effects of protein concentrate addition on the qualitative and quantitative composition of milk in organically farmed dairy cows. a total number of 40 holstein cows were divided into two groups. live weight of dairy cows was around 625±25 kg. average production efficiency of animals was 7600±50 kg milk for the lactation period. Animals of both groups received identical basal feed ration. The first experimental group of cows (n=20) received in the feed ration a protein concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Dairy cattle kept in a free-stall system spend their entire lives in a barn, so a caretaker should provide everything that is optimal for their welfare (Gody n et al 2013;Hempel et al 2016). Suitable temperature, humidity conditions, ventilation and ammonia concentration are particularly important because they affect the cows' rest conditions, their behaviour, hormonal and metabolic changes and milk production (Herbut & Angrecka 2014;Horky 2014;Herbut et al 2015). One of the behavioural characteristics being an indicator of the cows' physiological and health state is their locomotor activity and the length of lying and standing bouts (Tolkamp et al 2010;Rado n et al 2014;Angrecka & Herbut 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Dairy cattle kept in a free-stall system spend their entire lives in a barn, so a caretaker should provide everything that is optimal for their welfare (Gody n et al 2013;Hempel et al 2016). Suitable temperature, humidity conditions, ventilation and ammonia concentration are particularly important because they affect the cows' rest conditions, their behaviour, hormonal and metabolic changes and milk production (Herbut & Angrecka 2014;Horky 2014;Herbut et al 2015). One of the behavioural characteristics being an indicator of the cows' physiological and health state is their locomotor activity and the length of lying and standing bouts (Tolkamp et al 2010;Rado n et al 2014;Angrecka & Herbut 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of dairy farming is to achieve the highest possible milk yield while maintaining the welfare of the animals by, for example, suitable microclimate of the building (Albright and Timmons 1984;Cook et al 2005) especially in the case of meeting the essential cows' needs, such as constant access to food and water and/or relative changeless time of milking (Adamczyk et al 2011;Horky 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that the mean of S/C was lower and CR was higher both significantly (P<0.05) in dairy cattle having BUN<18 than those of with BUN>18 mg/dL (Table 2). Urea nitrogen in cow body fluids largely derives from a high protein intake of feed; the addition of concentrate in dairy feed will affect the quality and composition of milk (19). Increased feeding of high rumen degradable protein in dairy cows through the addition of concentrates potentially increases milk production by increasing protein synthesis in rumen (20).…”
Section: Resultsmentioning
confidence: 99%